2014
DOI: 10.1007/s12016-013-8406-7
|View full text |Cite
|
Sign up to set email alerts
|

Cogan's Syndrome—Clinical Guidelines and Novel Therapeutic Approaches

Abstract: Cogan's syndrome (CS) is a rare chronic inflammatory disorder, classically characterized by interstitial keratitis and sensorineural hearing loss. Recurrent episodes of inner ear disease might result in deafness. In some patients, it may also be accompanied by systemic vasculitis. Diagnosis of CS is often missed or delayed due to its rarity, the nonspecific clinical signs at onset, and the lack of a confirmatory diagnostic test. The mechanisms responsible for CS are unknown; however, in the last decade, the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 44 publications
1
31
0
3
Order By: Relevance
“…Similarly, in humans with immune‐mediated hearing loss, we identified elevated TNF levels to be largely predictive of steroid‐sensitive, immune‐mediated hearing loss . Tumor necrosis factor antagonism appears to have therapeutic benefit in Cogan syndrome patients and several other small cohorts with AIED by intratympanic injection; however, in another placebo‐controlled study of successful corticosteroid‐treated AIED patients, TNF antagonism by intravenous infusion was no better than placebo . Why is there a disparity?…”
Section: Methodsmentioning
confidence: 87%
“…Similarly, in humans with immune‐mediated hearing loss, we identified elevated TNF levels to be largely predictive of steroid‐sensitive, immune‐mediated hearing loss . Tumor necrosis factor antagonism appears to have therapeutic benefit in Cogan syndrome patients and several other small cohorts with AIED by intratympanic injection; however, in another placebo‐controlled study of successful corticosteroid‐treated AIED patients, TNF antagonism by intravenous infusion was no better than placebo . Why is there a disparity?…”
Section: Methodsmentioning
confidence: 87%
“…11 Certain patients may require longterm corticosteroid therapy because of the recurrent hearing loss during attempts to taper the prednisone dose, 1 so, azathioprine, cyclophosphamide, cyclosporine, methotrexate, and tumor necrosis factor (TNF)-alpha blockers have been recommended. 4,12,13 Some patients may show unresponsiveness to such a therapy, thereby resulting in severe hearing loss as in our case.…”
Section: Discussionmentioning
confidence: 69%
“…3,4 The ocular involvement in CS usually gives a good response to topical corticosteroid therapy, while, systemic corticosteroids are reserved for unresponsive cases or those with posterior uveitis, it was reported that poor long term ophthalmologic outcomes due to CS are unusual in contrast to vestibuloauditory affection. 3,7 Deafness is the most common serious outcome of CS and systemic corticosteroid therapy is warranted as soon as possible after the onset of hearing loss, 5,6,12,14 with the recommendation of an initial dose therapy of 1 mg/kg (0.5-2) per day of prednisone. 4 If an improvement in hearing is observed (objectively and subjectively), corticosteroids are gradually tapered over 2-6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids are the mainstay of treatment for sensorineural hearing loss and may be effective if they are administered early [15], but there is little consensus in the literature about the utility of additional immunosuppressive agents for these symptoms. Azathioprine, methotrexate, cyclosporine, and cyclophosphamide have been used with varying success; treatment with infliximab in refractory cases has shown promising results [16]. In 2010, Orsoni et al described the case of a 25-year-old Italian woman with interstitial keratitis and bilateral sensorineural hearing loss whose hearing did not improve despite treatment with corticosteroids, cyclophosphamide, methotrexate, cyclosporine, and adalimumab.…”
Section: Discussionmentioning
confidence: 99%